Using IMUs to Identify Supervisors on Touch Devices - Kharrufa, Ahmed; Nicholson, James; Dunphy, Paul; Hodges, Steve; Briggs, Pam; Olivier, Patrick (Interact 2015, 2015)
In addition to their popularity as personal devices, tablets, are becoming increasingly prevalent in work and public settings. In many of these newly-established application domains a supervisor user – such as the teacher in a classroom – oversees the function of one or more devices. Access to supervisory functions is typically controlled through the use of a passcode, but experience shows that keeping this passcode secret can be problematic. In this paper we introduce SwipeID, a method of identifying supervisor users such as teachers across a set of touch-based devices by correlating data from a wrist-worn inertial measurement unit (IMU) and a corresponding touchscreen interaction. This approach naturally supports access at the time and point of contact and does not require any additional hardware on the client devices. We describe the design of our system and the challenge-response protocols we have considered. We then present an evaluation implemented using capacitive touchscreens to demonstrate feasibility. Finally we highlight the potential for our scheme to extend to different application domains and other input devices such as the mouse.